Longitudinal Flow Decorrelations in Xe+Xe Collisions at sqrt[s_{NN}]=5.44 TeV with the ATLAS Detector - Aad, G; Abbott, B; Abbott, D C; Abed Abud, A; Abeling, K; Abhayasinghe, D K; Abidi, S H; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abulaiti, Y; et al. (Physical review letters, 2021)
The first measurement of longitudinal decorrelations of harmonic flow amplitudes v_{n} for n=2-4 in Xe+Xe collisions at sqrt[s_{NN}]=5.44 TeV is obtained using 3 μb^{-1} of data with the ATLAS detector at the LHC. The decorrelation signal for v_{3} and v_{4} is found to be nearly independent of collision centrality and transverse momentum (p_{T}) requirements on final-state particles, but for v_{2} a strong centrality and p_{T} dependence is seen. When compared with the results from Pb+Pb collisions at sqrt[s_{NN}]=5.02 TeV, the longitudinal decorrelation signal in midcentral Xe+Xe collisions is found to be larger for v_{2}, but smaller for v_{3}. Current hydrodynamic models reproduce the ratios of the v_{n} measured in Xe+Xe collisions to those in Pb+Pb collisions but fail to describe the magnitudes and trends of the ratios of longitudinal flow decorrelations between Xe+Xe and Pb+Pb. The results on the system-size dependence provide new insights and an important lever arm to separate effects of the longitudinal structure of the initial state from other early and late time effects in heavy-ion collisions.